2015
DOI: 10.1109/tmtt.2015.2432766
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Mode Theory Applied to Resonators in the Presence of Conductors

Abstract: Using the method of images, Energy Coupled Mode Theory (ECMT), a coupled mode equation in the frequency domain, is extended to deal with important cases where resonators are in close proximity to conducting surfaces. Depending on the type of conductors and the orientation of the resonators, the method of images determines the relative phases of the images. Using the formed images, the coupled frequencies and fields can be determined by applying ECMT. Two cases are studied. In the first case, it is shown that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Coupling coefficient is a key parameter for many electric devices, such as microwave filters, electron paramagnetic resonance probes, stereometamaterials and WPT systems [13][14][15]. The coupling coefficient mainly describes the strength of energy exchange between the resonators.…”
Section: Methods To Obtain the Coupling Coefficient And The Electric Amentioning
confidence: 99%
“…Coupling coefficient is a key parameter for many electric devices, such as microwave filters, electron paramagnetic resonance probes, stereometamaterials and WPT systems [13][14][15]. The coupling coefficient mainly describes the strength of energy exchange between the resonators.…”
Section: Methods To Obtain the Coupling Coefficient And The Electric Amentioning
confidence: 99%
“…Furthermore, the excitation of symmetric and asymmetric resonances was reported not only using metasurfaces with a large number of resonators, but also with a single resonator inside a rectangular waveguide system [ 47 , 48 , 49 ]. As a result of the coupling between the resonator inside the waveguide and its mirror images that were enabled by the metallic walls of the waveguide, the collective behavior of the full metasurface was achieved [ 50 , 51 , 52 ]. Moreover, the system was very compact, and the measurements were more robust compared with a full metasurface.…”
Section: Introductionmentioning
confidence: 99%
“…No matter which coupling is utilized, it is necessary to maintain the strength of coupling between the transmitting and receiving elements at a certain level. Some research works have been reported on the study of electromagnetic coupling between RF devices [11][12][13][14][15]. Quantitative data on the electric and magnetic coupling components reveal the nature of coupling between the transmitting and receiving elements.…”
Section: Introductionmentioning
confidence: 99%